PERLINDUNGAN PELAKU USAHA MIKRO, KECIL DAN MENENGAH MELALUI POLA KEMITRAAN, KEAGENAN DAN DISTRIBUSI DALAM PERSPEKTIF HUKUM PERJANJIAN - U. Sudjana (Lembaga Kajian Hukum, Fakultas Hukum, Universitas Singaperbangsa Karawang, 2019)
The micro, small and medium enterprises actors in the partnership pattern do not have a bargaining position because the agreement clause is determined unilaterally by the principal, so that the micro small and medium enterprises players are harmed. Therefore, this study aims to determine the protection of agents and distributors as micro small and medium enterprises through the partnership pattern in the perspective of agreement law. The research method was carried out with a normative juridical approach to the research phase of library research using qualitative normative data analysis. The results of the study show that the characteristics and legal relationships in the agency and distribution agreements are included between the lease agreement and the sale and purchase agreement, so that the general provisions of the Civil Code can be applied to both patterns of partnership in addition to special provisions. The MSMEs in the agency and distribution partnership pattern in the perspective of a normative agreement have received protection because every national trading company that makes an agreement with the principal of goods or services produced abroad or domestically as an agent and distributor must be registered at the Ministry of Trade to obtain a Registration Certificate.